Acceptability of a Fentanyl Vaccine to Prevent Opioid Overdose and Need for Personalized Decision-Making . (17th May 2022) - Weitzman, Elissa R; Kossowsky, Joe; Blakemore, Laura M; Cox, Rachele; Dowling, David J; Levy, Ofer; Needles, Emma W; Levy, Sharon
Abstract: Background: The opioid epidemic worsened during the coronavirus disease 2019 (COVID-19) pandemic. Synthetic opioids (primarily fentanyl) comprise the most common drugs involved in overdose (OD) death. A vaccine that blocks fentanyl from reaching the brain to prevent OD is under development, and insight is needed into its acceptability. Methods: Using a semi-structured interview guide, persons with opioid use disorder (OUD), family, professionals, and the public were interviewed about attitudes and concerns regarding a fentanyl vaccine. Reactions to fictional clinical vignettes of persons at risk of OUD because of pain and/or substance use histories were collected, analyzed, and quantified for favorability. Interviews were transcribed, coded, and analyzed thematically. Results: Among N = 64 participants, (70.3% female, average age 32.4 years), attitudes were favorable toward a fentanyl vaccine, with preference for lifelong durability (76% of n = 55 asked). Perceived benefits centered on the potential for a life-saving intervention, suffering averted, healthcare dollars saved, and the utility of a passive harm reduction strategy. Concerns centered on uncertainty regarding vaccine safety, questions about efficacy, worry about implications for future pain management, stigma, and need for supportive counseling and guidance to personalize decision making. Reactions to vignettes revealed complex attitudes toward fentanyl vaccination when considering recipient age, health history, and future risks for addiction and pain. Conclusions: Positive responses to a fentanyl vaccine were found along with appreciation for the complexity of a vaccine strategy to prevent OD in the setting of pain and uncertain durability. Further research is needed to elucidate operational, ethical, and communications strategies to advance the model. Abstract : Persons with opioid use disorder and members of the public shared positive attitudes toward a fentanyl vaccine to block overdose, and identified concerns regarding stigma, pain management, and uncertain durability. Findings suggest need for concerted attention to implementation and communications.